Cycloaddition Strategies for the Synthesis of Diverse Heterocyclic Spirocycles for Fragment‐Based Drug Discovery. Issue 31 (29th July 2019) - King, Thomas A.; Stewart, Hannah L.; Mortensen, Kim T.; North, Andrew J. P.; Sore, Hannah F.; Spring, David R.
Abstract : In recent years the pharmaceutical industry has benefited from the advances made in fragment‐based drug discovery (FBDD) with more than 30 fragment‐derived drugs currently marketed or progressing through clinical trials. The success of fragment‐based drug discovery is entirely dependent upon the composition of the fragment screening libraries used. Heterocycles are prevalent within marketed drugs due to the role they play in providing binding interactions; consequently, heterocyclic fragments are important components of FBDD libraries. Current screening libraries are dominated by flat, sp 2 ‐rich compounds, primarily owing to their synthetic tractability, despite the superior physicochemical properties displayed by more three‐dimensional scaffolds. Herein, we report step‐efficient routes to a number of biologically relevant, fragment‐like heterocyclic spirocycles. The use of both electron‐deficient and electron‐rich 2‐atom donors was explored in complexity‐generating [3+2]‐cycloadditions to furnish products in 3 steps from commercially available starting materials. The resulting compounds were primed for further fragment elaboration through the inclusion of synthetic handles from the outset of the syntheses. Abstract : Heterocyclic spirocycles represent a promising region of chemical space for fragment‐based drug discovery, combining the advantages of heteroatoms and three‐dimensionality. The sterically‐crowded quaternary carbon centre has historically provided a significant synthetic challenge. This work explores the application of cycloaddition reactions as a solution in the synthesis of heterocyclic spirocycles.